Avaliação do concreto geopolimérico como substituto do concreto de cimento portland: resistência mecânica, resistência ao fogo e ACV - Lima, Paulo Henrique Alves de (2021)
High energy consumption and high carbon dioxide emissions are the biggest problems in the Portland cement industry related to environmental pollution. In this scenario, geopolymeric concrete (CG) emerges as a potential substitute for Portland cement concrete (CCP). In addition to its environmental potential, this alternative concrete has similar mechanical characteristics when compared to the conventional solution, also presenting the advantage of having an initial gain of resistance superior to Portland cement concrete, are also pointed out by some researchers interesting thermomechanical properties, which makes reinforced concrete structures safer when exposed to fire situations. Thus, this study aims to verify the possible advantages of geopolymeric concrete against Portland cement concrete, through material characterization tests, mechanical and thermal tests and evaluating CO2-eq emission and energy expenditure through life cycle evaluation (LCA) taking as base unit 1m³ of each material. It was observed that the geopolymeric concrete reached more than 95% of its final resistance in the first 7 days of curing, which for the adopted trait, obtained a final resistance higher than 50MPa. In addition to mechanical strength, geopolymeric concrete presents a lower mass loss than conventional concrete when exposed to high temperatures (up to 1200ºC), at 28 days, CG has a mass loss of only 8.52% while the CCP presents a mass loss of more than 25%. When comparing the emission in kg of CO2-eq, it is observed that the alternative concrete has a 53.94% lower emission than the conventional concrete, but with a higher energy consumption. Thus, it is possible to affirm that geopolyphenic concrete has a great potential for insertion within civil construction as a substitute for Portland cement-based concrete, both from the point of view of thermomechanical performance and in the mitigation of environmental impacts.